Cost of care for patients on maintenance haemodialysis in public facilities in Cameroon - Halle, Marie Patrice; Jimkap, Natacha Nono; Kaze, Francois Folefack; Fouda, Hermine; Belley, Eugene Priso; Ashuntantang, Gloria (African Journal of Nephrology, 2017)
Background: The management of end-stage kidney disease constitutes a heavy burden on communities worldwide due to the high cost of renal replacement therapy (RRT). Data on the cost of RRT are scanty in low-income countries. This study aimed to evaluate the global cost of haemodialysis in Cameroon, an emerging economy in Central Africa. This will provide data to help healthcare planners develop more cost-effective strategies for the care of these patients. Methods: A prospective cost analysis of chronic haemodialysis care in three public-sector facilities was conducted in Cameroon. Both incident and prevalent patients were enrolled and followed up for 6 months. Patient data and costs were collected from patient interviews, medical records, bills, hospital price-lists and the procurement departments of the hospitals. Direct medical costs included outpatient consultation fees, dialysis consumables, dialysis session fees, drugs, laboratory and radiological tests. Non-medical direct costs included the cost of transport, feeding, water and electricity. Indirect costs related to the monthly loss of productivity for patients and their caretakers. The annual costs were calculated as the median costs for 6 months multiplied by 2 and were expressed in the local currency, the Central African franc (XAF), and US dollars (). Results: A total of 154 patients (62.3% males), mean age of 46.8 ± 15.2 years, were included, with 6 130 dialysis sessions completed during the study period. The annual median cost of haemodialysis per patient was XAF 7 988 800 ( 13 581). Out-of-pocket payments amounted to XAF 2 420 300 ( 4 114), accounting for 30% of the total cost. The median direct cost was XAF 7 458 200 ( 12 679) and indirect cost XAF 530 600 ( 902). Direct medical costs accounted for 88%, mainly due to dialysis consumables. In the initiation phase, additional costs of 754 were incurred. The cost of hospitalization, laboratory and radiology tests, feeding, consultation fees and some drugs varied significantly among facilities. Conclusions: Compared to the national gross domestic product per capita in Cameroon, the cost of care of patients on haemodialysis is high. Out-of-pocket payments are out of the reach of most patients and there is a need for implementing other cost-effective strategies to prevent and manage end-stage kidney disease in our setting. Key words: cost analysis, haemodialysis, peritoneal dialysis, Cameroon.